Effects of Spiritual Interventions on Happiness Level of the Female Elderly Residing in Nursing Home - Toktam Ayyari; Raha Salehabadi; Sedighe Rastaghi; Mostafa Rad (Mashhad University of Medical Sciences, 2020)
Background: Spiritual health is one of the dimensions of health. Currently, studies have identified a link between happiness and spiritual health; however, the effects of spiritual interventions on happiness have not been evaluated among the elderly. Aim: This study aimed to evaluate the effects of spiritual interventionson the happiness of the female elderly.   Method: A total of 40 subjects were randomly allocated to two intervention and control groups in Madar Nursing Home in Sabzevar, Iran, in 2019. In the intervention group, spiritual interventionswere performed as active listening, supporting religious rituals, using supportive systems, and arousing hope for 4 weeks. The happiness level of the participants was assessed before, immediately after, and a month after the intervention using the Oxford Happiness Questionnaire. Data analysis was performed by SPSS software (version 21) using descriptive and inferential statistics. Results: The mean scores of happiness before the intervention were 45.6±1.2 and 36.5±11.9 in the intervention and control groups, respectively. However, the scores altered to 65.1±9.9 and 35.3±9.4 immediately after the intervention, as well as 64.7±9.7 and 35.1±8.9 a month following the intervention, in the intervention and control groups, respectively. The repeated measures analysis of variance indicated a significant difference among the groups by determining the effect of the happiness score before the intervention (P<0.0001). Implications for Practice: According to the obtained results, spiritual interventions increased the happiness level of the female elderly. Therefore, it is concluded that spiritual interventions can be considered practical approaches to improve the happiness of the elderly.